Observation of *Supported in part by National Key R&D Program of China under Contracts Nos. Supported in part by National Key R&D Program of China (2020YFA0406300, 2020YFA0406400); National Natural Science Foundation of China (NSFC) (11975118, 11625523, 11635010, 11735014, 11822506, 11835012, 11935015, 11935016, 11935018, 11961141012, 12022510, 12025502, 12035009, 12035013, 12061131003, 12075252, 12192260, 12192261, 12192262, 12192263, 12192264, 12192265); the Natural Science Foundation of Hunan Province of China (2019JJ30019); the Science and Technology Innovation Program of Hunan Province (2020RC3054); the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program; Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1732263, U1832207); CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH040); 100 Talents Program of CAS; INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; ERC (758462); European Union Horizon 2020 research and innovation programme under Contract No. Marie Sklodowska-Curie grant agreement (894790); German Research Foundation DFG (43159800), Collaborative Research Center CRC 1044, FOR 2359, GRK 2149; Istituto Nazionale di Fisica Nucleare, Italy; Ministry of Development of Turkey (DPT2006K-120470); National Science and Technology fund; Olle Engkvist Foundation (200-0605); STFC (United Kingdom); The Knut and Alice Wallenberg Foundation (Sweden) (2016.0157); The Royal Society, UK (DH140054, DH160214); The Swedish Research Council; U. S. Department of Energy (DE-FG02-05ER41374, DE-SC-0012069). (1st April 2023) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Adlarson, P.; Albrecht, M.; Aliberti, R.; Amoroso, A.; An 安, M. R. 美儒; An 安, Q. 琪; Bai 白, X. H. 旭红; Bai 白, Y. 羽; Bakina, O.; Baldini Ferroli, R.; et al.
Abstract: Using data taken at 29 center-of-mass energies between 4.16 and 4.70 GeV with the BESIII detector at the Beijing Electron Positron Collider corresponding to a total integrated luminosity of approximately 18.8, the process is observed for the first time with a statistical significance of . The average Born cross sections in the energy ranges of (4.160, 4.380) GeV, (4.400, 4.600) GeV and (4.610, 4.700) GeV are measured to be fb, fb and fb, respectively, where the first uncertainties are statistical and the second are systematic. The line shapes of the and invariant mass spectra are consistent with phase space distributions, indicating that no hexaquark or di-baryon state is observed.